Case Report of Multiple Tracheostomy Revisions due to Persistent, Recurrent Cuff Leak - Azimi-Bolourian, Jian P.; Williams, George W.; Hanna, Issa A. (Case reports in anesthesiology, 2015)
This case is a patient with amyotrophic lateral sclerosis who was unable to be separated from mechanical ventilator support and required a tracheostomy. The patient underwent an initial open tracheostomy utilizing flexible fiberoptic tracheoscopy (FFT) in the operating room (OR). Subsequently, he developed recurrent leaks in the tracheal tube cuff requiring multiple trips back to the operating room. The recurrent cuff leak occurred following each tube placement until the etiology of the leak was discovered during the fourth procedure. In the fourth procedure, the wound was explored more extensively, and it was found that there was a sharp, calcified, aberrant fragment of a tracheal cartilage ring protruding into the tracheal lumen, which was damaging the cuff of each tube. This fragment was not visible by multiple FFTs, nor was it visible in the wound by the surgeons until wider exploration of the wound occurred. The cartilage fragment was ultimately excised and the patient had no further cuff leaks. Aberrant tracheal cartilage should be on the differential diagnosis for cuff leaks subsequent to surgical tracheostomy (ST) or percutaneous dilatational tracheostomy (PDT).